Peluang Usahatani Vanili Di Pulau Lombok - Rakhmad Wahyuningsih; Taslim Sjah; Hayati Hayati (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Vanilla is one type of plantation crop that has high economic value with a relatively stable price compared to other plantation crops. Vanilla has a fairly high economic value because of the demand for its fruit extract which is known as a source of fragrance ingredients in food and beverages. This study applied secondary data collection, in collecting data from West, North, and East Lombok. Data were analyzed with AWOT Analysis, based on strengths, weaknesses, opportunities and threats. The results showed that vanilla farming on the island of Lombok has a great opportunity to be developed because it has high demand from domestic and international markets. Indonesian vanilla is much favored by consumers both from within the country and abroad. This is because the quality of vanilla in Indonesia is superior to that of vanilla from Mexico and Madagascar, which are also well-known as producers of high-quality vanilla, vanilla for export. In addition, Lombok Island is a producer of organic vanilla which has been carried out since 2020, thereby increasing its selling value and vanilla in NTB is a strategic superior commodity to be developed because it has international market quality and vanilla in NTB has been recognized as one of the best in the world.